HUBUNGAN EFEKTIVITAS KERJA DENGAN KEPUASAN KERJA PADA KARYAWAN DI PT. SINAR NIRWANA SARI SAMARINDA - Handono, Tri Mei (MOTIVASI, 2013)
Tri Mei Handono. 08.11.1001.3510.028. Fakultas Psikologi Program Studi Psikologi. Universitas 17 Agustus 1945 Samarinda, 2013. This study aims to reveal the effectiveness of working relationships with employee job satisfaction in PT Sinar Nirwanasari Samarinda. No matter how small changes in the effectiveness of the work will affect the job satisfaction of employees. Individual behavior will be correlated with job satisfaction. The population in this study were employees working at PT. Samarinda Nirwanasari rays. As many as 78 samples were taken from 110 respondents of the existing population. Non-parametric correlation test using the product moment correlation coefficient to determine the relationship between variables X and Y values by comparing the count r with r table. From the calculations, r of 0.7013. After the results of the analysis are compared with the r table (table critical value) where N = 78 with a significance level of 0.05, it turns out empirical count r is greater than r table (0.7013> 0.220> 0.286). Thus the working hypothesis (hi) be accepted as true and reject the null hypothesis (ho). This means that there is a significant relationship between effectiveness and job satisfaction in employees of PT. Nirwanasari ray Samarinda